The old Greek translation of Zechariah - Eidsvåg, Gunnar Magnus, 1977- (Vetus Testamentum, Supplements Ser., 2015)
The Old Greek translation of Zechariah has not received much scholarly attention even though it contains several well known passages. Questions concerning its origin and character as a translation have yet to be dealt with in a comprehensive manner. The present monograph aims to bridge this gap by offering new methodological perspectives. The Old Greek Translation of Zechariah attempts to answer questions concerning the outlook of the translation, and what faction of the Jewish society was interested in translating this book into Greek. It argues that the translator had pro-Hasmonean sympathies.